Concomitant use of interleukin-2 and tacrolimus suppresses follicular helper T cell proportion and exerts therapeutic effect against lupus nephritis in systemic lupus erythematosus-like chronic graft versus host disease - Nasa, Yutaro; Satake, Atsushi; Tsuji, Ryohei; Saito, Ryo; Tsubokura, Yukie; Yoshimura, Hideaki; Ito, Tomoki (Frontiers in Immunology, 2024)
Introduction: Defective interleukin-2 (IL-2) production contributes to immune system imbalance in patients with systemic erythematosus lupus (SLE). Recent clinical studies suggested that low-dose IL-2 treatment is beneficial for SLE and the therapeutic effect is associated with regulatory T cell (Treg) expansion. Pharmacological calcineurin inhibition induces a reduction in the number of Tregs because they require stimulation of T cell receptor signaling and IL-2 for optimal proliferation. However, the activation of T cell receptor signaling is partially dispensable for the expansion of Tregs, but not for that of conventional T cells if IL-2 is present. Aim: We examined whether addition of IL-2 restores the Treg proportion even with concurrent use of a calcineurin inhibitor and if the follicular helper T cell (Tfh) proportion is reduced in an SLE-like murine chronic graft versus host disease model. Methods: Using a parent-into-F1 model, we investigated the effect of IL-2 plus tacrolimus on Treg and Tfh proportions and the therapeutic effect. Results: Treatment with a combination of IL-2 and tacrolimus significantly delayed the initiation of proteinuria and decreased the urinary protein concentration, whereas tacrolimus or IL-2 monotherapy did not significantly attenuate proteinuria. Phosphorylation of signal transducer and activator of transcription 3, a positive regulator of Tfh differentiation, was reduced by combination treatment, whereas phosphorylation of signal transducer and activator of transcription 5, a negative regulator, was not reduced. Conclusion: Addition of calcineurin inhibitors as adjunct agents may be beneficial for IL-2-based treatment of lupus nephritis.